AN ANNOTATED TRANSLATION OF A BABY FOR REBECCA BY TRISHA ALEXANDER - Ayuningtyas, Puti N.; Said, Mashadi (Universitas Gunadarma, 2017)
This is an annotated translation research. The methods employed in this research are introspective and retrospective methods. The outcomes of this research showed that of 100 difficulties of 68 items of lexicon, 19 items of grammatical structure, 9 items of communication situation, and 4 items of cultural context found in this research, 25 items of the difficulties were annotated and were categorized into 17 items of lexicon, 5 items of grammatical structure, 2 items of communication situation, and 1 item of cultural context. The researcher solved the problems by using relevant translation theories, principles, and strategies as well. Based on the 25 items which had been annotated by the researcher, it was found that there were 14 translation strategies, namely 4 items of cultural filtering, 2 items of paraphrase, 1 item of emphasis change, 3 items of transposition, 2 items of synonymy, 2 items of distribution change, 1 item of literal translation, 2 items of hyponymy, 3 items of explicitness change, 1 item of clause structure changes, 1 item of phrase structure changes, 1 item of abstraction change, 1 item of interpersonal change and 1 item of calque used by the researcher to solve the difficulties in translating the source text into the target language. It can be concluded that in translating a novel entitled A Baby for Rebecca, the translator encountered some difficulties and to solve the problems of the difficulties, the translator employed translation theories, principles and strategies. This suggests the necessity for the translator to have adequate understanding of translation theories, principles, and strategies in the course of translation. Keywords: Annotation, Translation Theory, Translation Principle, Translation Strategy